Microstructure and Water Retention Kinetics in Autogenous Cured Self-Compacting Concrete Blends Using Super Absorbent Polymer - Saavedra-Flores, E (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This research aimed to determine how a super absorbent polymer affects the microstructural characteristics and water retention kinetics of a new composite made by substituting granite pulver (GP) and fly ash (FA) for cement. Understanding the mechanics of water movement is crucial for comprehending the effectiveness of autogenous curing. Several experiments were conducted to analyze the water mitigation kinetics of super absorbent polymer (SAP) in the hydrating cement paste of autogenous cured self-compacting concrete (GP-ACSSC) mixtures. In the first hours following casting, water sorptivity, water retention, and hydration tests were carried out. The effects of various concentrations of SAP and GP, which was utilized as an alternative cement for the production of sustainable concrete that leads to reduction in carbon footprint, on the autogenous cured self-compacting concrete with reference to the abovementioned properties were explored. The investigation showed that releasing the curing water at a young age, even around the beginning of hydration, allowed homogenous and almost immediate distribution of water across the full cured paste volume, which improved the water retention kinetics. Compared to the control mixtures, the addition of SAP up to 0.6% and the substitution of cement with GP up to 15% had favorable impacts on all water kinetics parameters. © 2023 by the authors.